Reflections on the Peruvian Constitutional Court’s position regarding default interest in tax affairs - Durán Rojo, Luis (2023)
The peruvian Constitucional Court established a vinculant precedent about the inaplication of moratorium interest for tax debt due to the administration’s or judge delay in resolving people and companies demand’s. The autors explore the creation of precedents by the constitucional court, the nature of moratorium interest and analyzes, from the legal and constitutional perspective, if the inaplication of moratorium interest is a correct, proportional and reasonable solution for the administration or judge delay in resolving tax demand’s.